Involvement of microtubular network and its motors in productive endocytic trafficking of mouse polyomavirus. - Vojtech Zila (Public Library of Science (PLoS), 2014)
Infection of non-enveloped polyomaviruses depends on an intact microtubular network. Here we focus on mouse polyomavirus (MPyV). We show that the dynamics of MPyV cytoplasmic transport reflects the characteristics of microtubular motor-driven transport with bi-directional saltatory movements. In cells treated with microtubule-disrupting agents, localization of MPyV was significantly perturbed, the virus was retained at the cell periphery, mostly within membrane structures resembling multicaveolar complexes, and at later times post-infection, only a fraction of the virus was found in Rab7-positive endosomes and multivesicular bodies. Inhibition of cytoplasmic dynein-based motility by overexpression of dynamitin affected perinuclear translocation of the virus, delivery of virions to the ER and substantially reduced the numbers of infected cells, while overexpression of dominant-negative form of kinesin-1 or kinesin-2 had no significant impact on virus localization and infectivity. We also found that transport along microtubules was important for MPyV-containing endosome sequential acquisition of Rab5, Rab7 and Rab11 GTPases. However, in contrast to dominant-negative mutant of Rab7 (T22N), overexpression of dominant-negative mutant Rab11 (S25N) did not affect the virus infectivity. Altogether, our study revealed that MPyV cytoplasmic trafficking leading to productive infection bypasses recycling endosomes, does not require the function of kinesin-1 and kinesin-2, but depends on functional dynein-mediated transport along microtubules for translocation of the virions from peripheral, often caveolin-positive compartments to late endosomes and ER - a prerequisite for efficient delivery of the viral genome to the nucleus.